2017
DOI: 10.14382/epitoanyag-jsbcm.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the fresh selfcompacting concrete properties utilizing different types of additives

Abstract: self-compacting concrete (scc) is characterized by unique workability properties. stagnation or segregation of scc must be avoided to obtain a homogenous and stable mixture. When scc is produced, it is essential that the concrete has all the adequate fresh properties at the time of placement. For a successful and reliable application of scc, the predication of scc fresh state properties is of crucial importance. this predictability is determined by the sensitivity of the rheological properties towards the affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Processing window is a window created by mainly two coordinates, those coordinates are the slump flow (mm) in the x-axis and V-funnel time (s) in the y-axis, which could help to assess and limits the targeted values based on the upper and lower limits of the slump flow and for the V-funnel time tests. Some modifications have been suggested on the limited ranges EFNARC by a number of researchers who they investigated the fresh properties of SCHPC [16,17]. However, in the present study the suggested window EFNARC tested for its applicability in case of using RCA in the SCHPC.…”
Section: Processing Windowmentioning
confidence: 96%
See 1 more Smart Citation
“…Processing window is a window created by mainly two coordinates, those coordinates are the slump flow (mm) in the x-axis and V-funnel time (s) in the y-axis, which could help to assess and limits the targeted values based on the upper and lower limits of the slump flow and for the V-funnel time tests. Some modifications have been suggested on the limited ranges EFNARC by a number of researchers who they investigated the fresh properties of SCHPC [16,17]. However, in the present study the suggested window EFNARC tested for its applicability in case of using RCA in the SCHPC.…”
Section: Processing Windowmentioning
confidence: 96%
“…The ability of concrete to remain uniform during and after placement without any loss of stability due to bleeding, mortar separation and coarse aggregate settlement is the segregation resistance [12]. Choosing better grading of aggregates, decreasing the maximum aggregate size, using cementing materials with cement, and decreasing the w/b ratio enhances the segregation resistance [16,17], where in case of SCHPC the low segregation resistance decrease the durability of concrete [18].…”
Section: Segregation Resistancementioning
confidence: 99%
“…Perlite, a naturally occurring alumino-siliceous amorphous volcanic material derived from crude perlite rock, is commonly used in construction and is found in various countries, including Italy, Hungary, Turkey, Greece, Japan, and the United States [5][6][7]. The global production of perlite is increasing, driven by rising demand.…”
Section: Introductionmentioning
confidence: 99%